Keterpaduan Sistem Pendidikan Pesantren Dan Pendidikan Formal (Studi Analisis Di Pondok Pesantren Nur Arwani Buntet Pesantren Cirebon) - Riki Amirulloh (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Metro, 2022)
Development in today's society requires that the development of children be balanced between the conduct of values and morals, knowledge, intelligence, skills, communication skills, and attitudes toward the environment, in other words between technology science and the takwa faith should be balanced among today's children. The study is aimed at recognizing the application of the boarding system of boarding schools at the lodge of pesantren nur arwani, the application of formal education in the nur arwani lodge, and the integration of the salaf and formal boarding school system in the nur arwani lodge of global dynamic. It is a descriptive qualitative study. The data-gathering techniques used are observation, interviews, and documentation with valid data testing using triangulation techniques, using reference materials, member checks. Data analysis techniques run through several stages of data reduction, data presentation, deduction and verification. Results from this study suggest that (1) the application of a system of boarding school education in the gymnasium of nur arwani, can be seen from a applied curriculum, the materials taught. The methods used in learning, and the assessments of santri's study. (2) the application of formal education in the boarding house of pesantren nur arwani, can be seen by the applied curriculum, the materials taught. The methods used in learning, and the assessments of students' learning results. (3) the combination of the salaf and formal vocational education system can be reflected ina synergy between the boarding curriculum and the madrassa, managing the society, combining institutions in coping with global dynamics, and contributing factors and constraints.